Ductile fracture of aluminum 2024-T351 under proportional and non-proportional multi-axial loading: Bao–Wierzbicki results revisited. (September 2015) - Papasidero, Jessica; Doquet, Véronique; Mohr, Dirk
Abstract : Graphical abstract: Abstract: The effect of stress state and loading path on the ductile fracture of aluminum 2024-T351 is characterized through tension–torsion experiments on tubular specimens. The experimental program includes proportional and non-proportional loading paths leading to the onset of fracture at nearly plane stress conditions at stress triaxialities between 0 and 0.6. Stereo digital image correlation is used to measure the displacements and rotations applied to the specimen shoulders. An isotropic non-quadratic Hosford plasticity model with combined Voce–Swift hardening is used to obtain estimates of the local stress and strain fields within the specimen gage section. The hybrid experimental–numerical results indicate a higher strain to fracture for pure shear than for uniaxial tension. The calibration of a Hosford–Coulomb fracture initiation model suggests that the ductility of aluminum 2024-T351 decreases monotonically as a function of the stress triaxiality, whereas it is a non-symmetric convex function of the Lode angle parameter. It is shown that a simple non-linear damage accumulation rule can describe the effect of non-proportional loading on the strain to fracture.